If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 4b = 4b + 34 Combine like terms: 2b + 4b = 6b 6b = 4b + 34 Reorder the terms: 6b = 34 + 4b Solving 6b = 34 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. 6b + -4b = 34 + 4b + -4b Combine like terms: 6b + -4b = 2b 2b = 34 + 4b + -4b Combine like terms: 4b + -4b = 0 2b = 34 + 0 2b = 34 Divide each side by '2'. b = 17 Simplifying b = 17
| 15-4y-4y^2=0 | | 440.2908=2*52.7834+L | | 10-(x-2)=22 | | C=4*3.14 | | -(9-x)=12 | | yx^2+4xy+4y=0 | | 3-k=8 | | 69=-8-7(m+3) | | 14x-7=7+10x | | 22-4(3-x)=42 | | 36=(x+3)(x+3) | | 2x^2-10-x=0 | | 0.6x+4=20-x | | 0.6+4=20-x | | 12-w=157 | | 260-w=145 | | -4(b-3)=-44 | | 195=-x+1 | | 36=2x^2+6x+9 | | 4p-31+p+13=P+50 | | 3=-6v+3(v+8) | | -3(z+2)=24 | | 2n^2+n-36=0 | | x+3x+5=12 | | -2(c-1)=18 | | 4x^2+39x+171=0 | | w+12+2w+2=w+50 | | 2.5x-6=-4-3.5 | | -9x^9y^8(-4x^6z^7+3y^3+3z^8)= | | x^2+y^2-2x-8y-47=0 | | -9x^9y^8(-4x^6z^7+3y^3+3z^8)= | | 15x-48+5x=13x |